Decision-making framework for power system with RES including responsive demand, ESSs, EV aggregator and dynamic line rating as multiple flexibility resources - Erdinc, F. Gulsen; Cicek, Alper; Erdinc, Ozan; Yumurtaci, Recep; Oskouei, Morteza Zare; Mohammadi-Ivatloo, Behnam (ELSEVIER SCIENCE SA, 2022)
The carbon emissions emitted from conventional energy sources and the possibility of extinction of these sources in the near future push the states to seek new energy alternatives, namely renewable energy sources (RESs). In this respect, considering the increasing number of RESs thanks to the incentives of more environmentally friendly sources, and new generation loads, it is vital to use flexibility options in order to ensure reliability in the power systems. In this respect, this study deals with the stochastic optimum operating problem in a power system with wind power plants (WPPs), where dynamic line rating (DLR), pumped hydro energy storage (PHESS), common energy storage (CES), demand response (DR) and electric vehicle (EV) aggregator (EVAGG) is considered as flexibility options. With the proposed structure, an effective decision-making approach is presented that can meet all the requirements of power system operation, both technically and economically. Besides, various case studies carry out to demonstrate the effectiveness of the proposed framework in the IEEE 6-bus and IEEE 24-bus test system. According to the results obtained, PHESS has the most effect on minimization of wind spillage and total system operation cost, and when all flexibility options are evaluated, the total cost is significantly reduced, and no-load shedding occurs. The proposed model has a significant effect on reducing the total operation cost.
Keywords: Demand response; Dynamic line rating; Energy storage systems; Electric vehicle aggregator; Optimal operation of power system; Abbreviations, ces, Common energy storage; dlr, Dynamic line rating; ev, Electric vehicle; evagg, Electric vehicle aggregator; lse, Load serving entity; PHESS, Pumped hydro energy storage system; WPP, Wind power plant; RELIABILITY; Engineering